2017
DOI: 10.3390/ijms18040689
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Menstrual Blood-Derived Mesenchymal Stem Cells Promotes the Repair of LPS-Induced Acute Lung Injury

Abstract: Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are associated with high morbidity and mortality. Menstrual blood-derived stem cells (MenSCs) have been shown to be good therapeutic tools in diseases such as ovarian failure and cardiac fibrosis. However, relevant studies of MenSCs in ALI have not yet proceeded. We hypothesized that MenSC could attenuate the inflammation in lipopolysaccharide (LPS)-induced ALI and promote the repair of damaged lung. ALI model was induced by LPS in C57 mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 62 publications
(73 reference statements)
4
104
0
Order By: Relevance
“…In the present study, MCP-1 was suppressed in vitro in macrophages and in rat models of ALI after DFSC-CM treatment, which would contribute to the reduction of the infiltration of inflammatory cells in vivo. Our results are in good agreement with previous studies demonstrating that MCP-1 is essential for inflammatory infiltration in ALI [47,48] and other reports showing that MSC treatment remarkably decreased the injury score and neutrophil infiltration in the lung [30,49]. Our data demonstrated the antiinflammatory effects of DFSCs and DFSC-CM, at least to some extent, based on their ability to inhibit inflammatory infiltration.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the present study, MCP-1 was suppressed in vitro in macrophages and in rat models of ALI after DFSC-CM treatment, which would contribute to the reduction of the infiltration of inflammatory cells in vivo. Our results are in good agreement with previous studies demonstrating that MCP-1 is essential for inflammatory infiltration in ALI [47,48] and other reports showing that MSC treatment remarkably decreased the injury score and neutrophil infiltration in the lung [30,49]. Our data demonstrated the antiinflammatory effects of DFSCs and DFSC-CM, at least to some extent, based on their ability to inhibit inflammatory infiltration.…”
Section: Discussionsupporting
confidence: 83%
“…Recently, many studies reported that acute lung injury (ALI) animal model induced by Lipopolysaccharide (LPS) [29,30], which is a progressive clinical disease with high mortality and characterized by an excessive and uncontrolled inflammatory response, could be applied to test the immune-modulatory effects in vivo. The theory is that in the development of ALI, neutrophils and macrophages are activated to eliminate pathogens, however, it brings tissue damage by releasing antimicrobial compounds at the same time [31].…”
Section: Foxp3mentioning
confidence: 99%
“…Although our group has reported some clinical studies in H7N9 infected patients [6,12,15,36], understanding the detailed mechanism is still needed to reveal the potential for treating H7N9 induced ARDS. Along with our previous work [19,54,55], MSC has the ability to improve lung function through anti-inflammatory effects in acute injury lung in a mouse model. Thus, the underlying mechanism is probably that MSCs reduce the secretion of inflammatory factors.…”
Section: Discussionmentioning
confidence: 80%
“…The MSCs migration also depends on transplantation route. Most studies have used intravenous route [30,[35][36][37][38][39] and a large portion of the MSCs is trapped in the lungs during the first pass [40]. Escape from the lung trap may improve the survival of the MSCs and affect cell distribution and its therapeutic effects after transplantation.…”
Section: Therapeutic Function Mscsmentioning
confidence: 99%